A Lactose‐Derived CRISPR/Cas9 Delivery System for Efficient Genome Editing In Vivo to Treat Orthotopic Hepatocellular Carcinoma. Issue 17 (21st July 2020) - Qi, Yu; Liu, Yanli; Yu, Bingran; Hu, Yang; Zhang, Nasha; Zheng, Yan; Yang, Ming; Xu, Fu‐Jian
Abstract: Gene editing is a crucial and effective strategy to treat genetic diseases. Safe and effective delivery vectors are specially required for efficient gene editing in vivo of CRISPR/Cas9 system. Interestingly, lactose, a natural saccharide, can specifically bind to asialoglycoprotein receptors, highly expressed on the surface of hepatocellular carcinoma (HCC) cells. Herein, a lactose‐derived branched cationic biopolymer (LBP) with plentiful reducible disulfide linkages and hydroxyl groups is proposed as a potential delivery vector of CRISPR/Cas9 system for efficient genome editing in vivo to treat orthotopic HCC. LBP is synthesized via a facile one‐pot ring‐opening reaction. LBP possesses excellent compacting ability, degradability, biocompatibility, gene transfection performances, and HCC‐targeting ability. LBP‐mediated delivery of classical pCas9‐survivin, which can target and knockout survivin oncogene, produces efficient gene editing performances, and superb anti‐cancer activities in orthotopic HCC mouse models. This study provides an attractive and safe strategy for the rational design of CRISPR/Cas9 delivery system. Abstract : A polyhydroxy, reduction‐responsive degradable lactose‐derived branched cationic biopolymer is proposed as a safe and effective CRISPR/Cas9 delivery system for targeted therapy in orthotopic hepatocellular carcinoma.